Chlamydia trachomatis, Pelvic Inflammatory Disease, and Epithelial Ovarian Cancer. (16th August 2021) - Paavonen, Jorma; Turzanski Fortner, Renee; Lehtinen, Matti; Idahl, Annika
Abstract: Epidemiologic, clinical, molecular and translational research findings support an interrelationship between Chlamydia trachomatis, pelvic inflammatory disease (PID), and epithelial ovarian cancer (EOC). Overall, the link between C. trachomatis, PID, and EOC seems to be relatively weak, although nondifferential misclassification bias may have attenuated the results. The predominant tubal origin of EOC and the role of chronic inflammation in tumorigenesis suggest that the association is biologically plausible. Thus, C. trachomatis and PID may represent potential risk factors or risk markers for EOC. However, many steps in this chain of events are still poorly understood and need to be addressed in future studies. Research gaps include time of exposure in relation to the long-term consequences and lag time to EOC. Data of differential risk for EOC between chlamydial and nonchlamydial PID is also needed. Another major research gap has been the absence of high-performance biomarkers for C. trachomatis, PID, and EOC, as well as EOC precursors. Biomarkers for C. trachomatis and PID leading to increased risk of EOC should be developed. If the association is confirmed, C. trachomatis and PID prevention efforts may play a role in reducing the burden of EOC.